Peningkatan Minat Belajar Siswa pada Mata Pelajaran Bahasa Indonesia Melalui Model Inside Outside Circle (IOC) Kelas III SD Negeri 0514 SI Ali-Ali - Lailan Aprina Siregar; Era Mutiah; Irman Nst (Indo-MathEdu Intellectuals Journal, 2023)
This study aims to determine the increase in student interest in Indonesian language subjects through the inside outside circle model Class III SD Negeri 0514 SI Ali-Ali. The type used in this study is classroom action research. The data collection techniques used in this study were observation and tests. The source of data from this action research is 44 students of Class III SD Negeri 0514 Si Ali-Ali. The data obtained in this study was then analyzed to determine teacher activities and student development during learning. The results of data analysis showed that there was an increase in student interest in Indonesian language subjects through the inside outside circle model Class III SD Negeri 0514 SI Ali-Ali